Pengaruh Penggantian Sirup Glukosa dengan Sirup Sorbitol dan Penggantian Butter dengan Salatrim Terhadap Sifat Fisikokimia dan Organoleptik Kembang Gula Karamel - Netty Kusumawati, Thomas Indarto Putut Suseno, Nita Fibria, (Jurnal Teknologi Pangan dan Gizi, 2008)
Caramel soft candy is one of noncrysytalline candy, with soft and chewy texture. Sorbitol as known low calories sweetener agent with 2/3 Calorie content of sucrose. Salatrim is a one of fat replacer with lipid base was classified as triglyceride. The advantages of the salatrim usage is 5 Calories/gram compared with 9 Calories/gram on ordinary lipid together give physical characteristic with conventional lipid. This objective of this is to find out about the effect of the changing glucose syrup with sorbitol syrup and butter with salatrim toward chemical physics and organoleptic of caramel soft candy to know the usage of both to produce most favorable caramel soft candy. This study were doing with making caramel soft candy with replacement variation of glucose syrup with sorbitol syrup (20%:80%; 10%:90%; and 0%:100%) and replacement variation of butter with salatrim (10%:90 and 0%:100%). The study design are using Factorial Group Randomly Design and Factorial Complete Randomly Design with 6 treatment combination, each 4 replications. Based on statistic evaluation, there are interaction effect between replacement glucose syrup with sorbitol syrup and replacement butter with salatrim toward hardness, tensile strength and panelist preference to colour and texture caramel soft candy, but not effecting in water content, reducing sugar content, lightness, redness, yellowness and panelist preference to taste of caramel soft candy. Replacement glucoce syrup with sorbitol syrup would effecting in water content, reducing sugar content, lightness, redness and yellowness caramel soft candy. The taste preference effected by each of treatment but not effected by interaction of both treatment. The best product based on weighing technique was caramel soft candy with replacement glucose syrup with sorbitol syrup 100% and replacement butter with salatrim 100% (A3B2) that consists of 8,87% water content, 10,79 gram/ 100gram material, 487,25 Newton hardness, 10,13 Newton tensile strength, 41,48 lightness, 13,25 redness and 26,40 yellowness.The colour preference score was 5,04, texture was 5,07 and taste was 4,97 which classified on netral to likely enough.